REVIEW : HUBUNGAN MENGKONSUMSI KOPI DENGAN TEKANAN DARAH TINGGI - Fajar Surya Alam; Muhammad Ikhsan Prawira Negara (Jurnal Fakultas Teknik Kuningan, 2024)
Coffee is popular among various groups of teenagers, young adults and older people, both men and women. Apart from that, coffee is said to be a risk factor for hypertension. Because coffee contains caffeine. Caffeine has the property of increasing blood pressure. This study aims to determine the relationship between coffee and hypertension. This research uses a Literature Review design by collecting several journals via Google Scholar, and SINTA. In this study, people who have a habit of consuming moderate levels of coffee (600-800 ml) have a significant value (p value) of 0.010, where this value is smaller than the α value (0.05), so it can be concluded that there is a relationship between the frequency of coffee consumption and blood pressure in hypertensive patients in the working area of ​​the Dau Public Health Center, Malang Regency. If you look at the correlation coefficient (r), it is in the coefficient range of 0.40-0.599, namely 0.424, then the relationship between these variables is quite strong. There is a relationship between consuming coffee and blood pressure. It's just that the increasing frequency of coffee consumption will increase the increase in blood pressure.